Stems matter: Xylem physiological limits are an accessible and critical improvement to models of plant gas exchange in deep time - Matthaeus, William J.; Montañez, Isabel P.; McElwain, Jennifer C.; Wilson, Jonathan P.; White, Joseph D. (Frontiers in Ecology and Evolution, 2022)
The evolution of woody stems approximately 400 mya (middle Paleozoic) facilitated the expansion of plants and has likely affected carbon and water budgets across much of the terrestrial surface since that time. Stems are a carbon cost/sink and limit water transport from soil to leaves as it must pass through specialized xylem tissue. While leaf fossils have provided a wealth of quantitative data, including estimates of plant water fluxes utilizing biophysically based models, fossil-informed models integrating stem and leaf physiology are lacking. Integrated stem-leaf physiology may distinguish successors to ecological catastrophes like the end of the Late Paleozoic Ice Age (LPIA). The documented collapse of LPIA tropical forests provides an opportunity to assess the importance of woody stems as a key to understanding differences in survivorship among common plant taxa from the Carboniferous to the Permian. Here, we present an analysis of the limits to leaf water supply and plant function for Paleozoic forest plant types due to (1) cavitation-induced embolism and xylem blockage and (2) insufficient sapwood water transport capacity.—collectively defined here as sapwood dysfunction. We first present a modified ecosystem process model (Paleo-BGC+) that includes sapwood dysfunction. Paleo-BGC + is parameterized using measurements obtainable from fossil xylem and therefore applicable to both modern and ancient ecosystems. We then assess the effect of sapwood dysfunction on ecosystem processes based on previously published fossil leaf measurements and a new fossil xylem dataset for plant types present in the Late Paleozoic. Using daily meteorology from a GCM of the late Carboniferous (GENESIS v3) under a Glacial (low-CO2) and an Inter-glacial (high-CO2) scenario, we found that simulated sapwood dysfunction slowed plant water use and reduced carbon storage. This inhibition occurred particularly in plants with high maximum stomatal conductance and high stem vulnerability to embolism. Coincidentally, plants with these traits were predominantly reduced or missing from the fossil record from the Carboniferous to the Permian. Integrating stem and leaf physiology may improve the fidelity of model representations of soil-to-atmosphere water transport through plants, simulations of long-term climate phenomena like the LPIA, and ecosystem projections under future climate change.